Assessment of Residual Ridge Morphology among Edentulous Patients at A Tertiary Care Center of Nepal - Sapkota, Srijana Mishra; Thakur, Smriti Narayan; Rajbanshi, Mahesh Kumar (Journal of College of Medical Sciences-Nepal, 2024)
Background The morphology of the residual ridge is one of the predominant factors influencing denture retention, stability, support and the masticatory function in edentulous patients thereby affecting both the planning and treatment prognosis. This study was aimed to assess the different types of maxillary and mandibular residual ridge in the group of edentulous population in Chitwan, Nepal. Methods A descriptive cross-sectional study was conducted in total of 107 completely edentulous patients within the age of 55-85 years’ in Prosthodontic department of Chitwan Medical College. The type of maxillary and mandibular residual alveolar ridge in both male and female patients were noted in a predesigned proforma according to American College of Prosthodontists (ACP) classification system. The collected data was entered into Microsoft Excel and later transferred into SPSS version 26 and analyzed for descriptive statistics. Results In this study, 107 completely edentulous patients both male 63 (58.9%) and female 44 (41.1%) participated in the study. In the maxillary arch, Type B was most prevalent residual ridge type 55 (51.4%) whereas Type C in mandibular arch around 35 (32.7%). In male patients, Type B was most common 36 (57.1%) whereas Type A in female 20 (45.5%). Conclusions From this study it can be concluded that there is variation in the residual ridge. In maxillary arch, type B residual ridge was most prevalent followed by type A while in the mandibular arch type C was prevalent followed by type B.